Application of double-pulse laser-induced breakdown spectroscopy (DP-LIBS), Fourier transform infrared micro-spectroscopy and Raman microscopy for the characterization of copper-sulfides. Issue 2 (22nd December 2021) - Varotsis, Constantinos; Tselios, Charalampos; Yiannakkos, Konstantinos A.; Andreou, Charalampos; Papageorgiou, Marios; Nicolaides, Antonis
Abstract : Raman and FTIR microspectroscopies, laser induced breakdown spectroscopy (LIBS) and DP-LIBS have been applied towards our understanding of the characterization of the structure and structure–function relationship in copper-sulfide minerals. Abstract : The combined application of the structure sensitive techniques Fourier transform infrared μ-spectroscopy and Raman microscopy in conjunction with different approaches of laser-induced breakdown spectroscopy (LIBS) including the two-color double pulse (DP-LIBS) have been applied towards the characterization of whole ore copper-sulfide minerals. Discrete information from the surface of the whole ore minerals that lead to the establishment of infrared marker bands and from the surface of bioleached samples that allow the monitoring of jarosite and biofilm formation are provided by FTIR mapping experiments. Raman data can provide information related to the type of the mineral and of the secondary minerals formed on the surface of the ore. Of the four different LIBS approaches applied towards the characterization of the composition of the whole ore minerals, the DP-LIBS shows the highest sensitivity with increasing signals for both the Fe and Cu metals in the whole ore samples.